(untitled) (International Journal of Engineering and Computer Science, 2014)
Location tracking and updating are the fundamental issues in the moving objects.Object’s moving efficiency and location detection accuracy are taken into account in the project. The client sends the queries to the server based on the proper result. The server sends the reply to the client maintaining its accuracy as well as efficiency. Main strategies are to update the client request with the exact result. The advantage of this is the flexibility and ability to optimize the efficiency and also updating location of the moving object. We developed a system of high efficiency and accuracy to detect the exact location and also location updating technique for moving object.